Serum Metabolomic Patterns in Patients With Aldosterone-Producing Adenoma - Chen, Yule; Wang, Hanjiang; Wang, Ke; Zhu, Guodong; Yang, Zhishang; Wang, Min; Song, Wenbin (Frontiers in Molecular Biosciences, 2022)
Aldosterone-producing adenoma (APA), the main cause of secondary hypertension, has been reported recently to widely be involved in human diseases, such as metabolic syndrome, but the detailed mechanism remains unclear. Here, we compared the abundance of serum metabolites between essential hypertension (EHT) and APA, as well as the serum metabolites of APA patients before and after adrenalectomy, using untargeted metabolomics. Our results revealed 44 differential metabolites between APA and EHT patients, and 39 differential metabolites in APA patients before and after operation. Several metabolites involved in cardiovascular disease, obesity and diabetes were dysregulated in APA compared to EHT patients, including arachidonic acid metabolites (e.g., 5(S)-HpETE and 12-HETE), amino acids (e.g., L-carnitine, taurine and L-arginine), nucleotide metabolites (e.g., hypoxanthine) and cholesterol 3-sulfate. More importantly, hypoxanthine and cholesterol 3-sulfate, two metabolites promoting the development of atherosclerotic lesions and obesity, were upregulated in patients with APA but were reversed by adrenalectomy. Inversely, L-carnitine and (3-carboxypropyl) trimethylammonium cation, two metabolites participating in lipid metabolism, were decreased in APA patients but increased postoperatively. We concluded that APA might participate in cardiovascular and metabolic disease through regulating the serum metabolites.